Pengujian Validitas Media Pembelajaran Berbasis Android Pada Mata Pelajaran Adminitrasi Server Jaringan (ASJ) - Yuliawati Yunus; Indra Wijaya; Ihsanul Kamil (Universitas Putra Indonesia YPTK Padang, 2020)
This research was motivated by the problem of limited learning resources at SMKN 3 Padang. This research and development aims to produce a product in the form of Android-Based Learning Media at SMK N 3 Padang and to test the validity for the feasibility of the learning media product. This research uses research and development ((R&D) methods. This research method uses analysis (ADDIE Model), with the design and development steps as follows: Analysis (analysis), Design (design), Develop(development), Implementation (implementation ) and Evaluation (evaluation). for testing the validity of this study is at the Develop stage by using three validators as experts for the feasibility of Android-based learning media on ASJ subjects. The results of validity testing by experts. Learning based on Android is 80.00%, so the level of validity can be interpreted to be very valid to use. Based on the assessment and expert input and the results of field trials of Android-based learning media, it has been tested for feasibility, excellence, and can be used in the learning process at SMK N 3 Padang .